The Platelet Volume Distribution: A Signature of the Prethrombotic State in Coronary Heart Disease? - Trowbridge, E A; Martin, J F (Thrombosis and Haemostasis, 1987)
A coronary care unit population of 175 consecutive patients was studied. A clinical diagnosis of acute myocardial infarction was made in 103 cases (MI group) while 72 had chest pain, ECG indications of myocardial ischaemia, but no other clinical signs of acute myocardial infarction (control group). Based on bivariate Gaussian statistics the MI group could be divided in two groups, with respect to the platelet parameters of count and volume. The majority (65%) had large mean platelet volume and low count, while the remainder were indistinguishable from the control group. Patients with a large mean platelet volume also had significantly different volume distributions when assessed for volume dispersion, asymmetry and convexity. It is argued that this platelet volume distribution provides a signature for the prethrombotic state in ischaemic heart disease. Identification of such a platelet signature in a patient with coronary artery disease may allow appropriate prophylactic action to be taken and reduce the risk of subsequent acute myocardial infarction.
Keywords: Coronary heart disease; Platelet volume; Prethrombotic state